Growth Optima and Supply-Chain of the Walnut Crop in India - Hassan, Bakhtaver; Bhattacharjee, Mahua; Wani, Shabir A (Asian Journal of Agriculture and Rural Development, 2020)
This paper intends to study the Spatio-temporal growth of the walnut crop in Jammu & Kashmir, which holds a monopoly in walnut production in India. It also aims to assess the efficiency of the existing marketing channels of the walnut-crop in the region. A multi-stage random selection technique was used to collect primary data from three major walnut producing districts to identify the existing marketing channels and estimate their respective efficiencies. Compound-Annual-Growth-rate and Cuddy-Della-Valle index was used to estimate the growth of the walnut crop. Shepherd’s Marketing Efficiency Index was used to estimate the marketing efficiencies of the channels involved in the marketing of the crop. This paper found out very-high variability and slow growth in acreage, very-high variability, and high growth in production as well as in yield-per-hectare of the walnut crop.